2019
DOI: 10.3389/fnins.2019.00092
|View full text |Cite
|
Sign up to set email alerts
|

Adult Hippocampal Neurogenesis Can Be Enhanced by Cold Challenge Independently From Beigeing Effects

Abstract: In this study, we investigated the effects of cold challenge on adult hippocampal neurogenesis (AHN) and hippocampal gene expression and whether these are mediated by beigeing of peripheral fat tissues. Cold challenge (6 ± 2°C) for 1 and 4 weeks was found to induce beigeing effects in inguinal white adipose tissue based on hematoxylin and eosin staining as well as uncoupled protein-1 immunohistochemical staining. In the hippocampus, cold challenge for 1 or 4 weeks increased dentate gyrus neurogenesis and expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Those genes were found to cluster in two primary categories including biological process and molecular function ( Figure 4 A). The pathway enrichment analysis within the 5% genomic regions revealed that these genes were forcefully in connection with extreme environment adaptation-related pathways, including tight junction [ 27 , 28 ], notch signaling [ 29 , 30 , 31 ], vascular smooth muscle contraction [ 32 ], and RIG-I-like receptor signaling [ 33 , 34 ] ( Figure 4 B and Table 1 ). Within the consistent A/B compartment-switching regions, a series of genes related to cell proliferation and differentiation were identified in the tight junction, notch signaling, and RIG-I-like receptor signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those genes were found to cluster in two primary categories including biological process and molecular function ( Figure 4 A). The pathway enrichment analysis within the 5% genomic regions revealed that these genes were forcefully in connection with extreme environment adaptation-related pathways, including tight junction [ 27 , 28 ], notch signaling [ 29 , 30 , 31 ], vascular smooth muscle contraction [ 32 ], and RIG-I-like receptor signaling [ 33 , 34 ] ( Figure 4 B and Table 1 ). Within the consistent A/B compartment-switching regions, a series of genes related to cell proliferation and differentiation were identified in the tight junction, notch signaling, and RIG-I-like receptor signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, the tight junction and RIG-I-like receptor signaling pathways had been confirmed to exhibit a close connection with heat tolerance, with a fusion between immune and metabolic responses to ensure energy balance and permit growth and defense [ 28 , 33 ]. Interestingly, the notch signaling pathway was found to be involved in not only a high-temperature response [ 33 ], but also cold challenge [ 30 , 31 ], and played an extremely important role in the adaptation to hypoxic environments [ 30 ]. Vascular smooth muscle contraction, which includes vasoconstriction and vasodilation, contributes to cold acclimatization [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, Tight junction and RIG-I-like receptor signaling pathway had been verified having a close relationship with heat tolerance, with an integration between metabolic and immune responses to ensure energy balance and permit growth and defense (Bethany et al, 2018;Liu et al, 2017). Interestingly, Notch signaling pathway was found not only involving in high temperature response (Liu et al, 2017), but also had a strong correlation with cold challenge (Kim et al, 2019;Wang et al, 2012), and played an extremely important role in the adaption to hypoxic environment (Ishida et al, 2013). Vascular smooth muscle contraction that includes vasoconstriction and vasodilation is a process involved in cold acclimatization (Cardona et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We next explore the functional effects of 3D genome changes between LDC liver cells and WCC liver cells, we performed KEGG pathway analysis with genes located in the 5% genomic regions that switched between compartment B and compartment A in either direction (A=>B or B=>A) in both LDC and WCC liver cells. The pathway enrichment analysis showed these genes were strongly associated with extreme environment adaption-related pathways, including Tight junction (Bethany et al, 2018;Ying et al, 2015), Notch signaling pathway (Ishida et al, 2013;Kim et al, 2019;Wang et al, 2012), Vascular smooth muscle contraction (Cardona et al, 2014), RIG-I-like receptor signaling pathway (Liu et al, 2017;Zhang et al, 2018a) (Fig. 6 and Table 1).…”
Section: Chromatin Conformation and Gene Expression Changesmentioning
confidence: 99%